2021
DOI: 10.1002/chem.202102457
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Self‐Assembly of Gold Nanoparticles Based on Co‐Functionalization with Zwitterionic and Cationic Binding Motifs**

Abstract: We report a pH‐ and temperature‐controlled reversible self‐assembly of Au‐nanoparticles (AuNPs) in water, based on their surface modification with cationic guanidiniocarbonyl pyrrole (GCP) and zwitterionic guanidiniocarbonyl pyrrole carboxylate (GCPZ) binding motifs. When both binding motifs are installed in a carefully balanced ratio, the resulting functionalized AuNPs self‐assemble at pH 1, pH 7 and pH 13, whereas they disassemble at pH 3 and pH 11. Further disassembly can be achieved at elevated temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This limits their applications in the field of biology and smart materials. The fabrication of NP assemblies featuring multiple "artificial atoms", well-organized configurations, and responsiveness to external stimuli such as solvents, [15] temperature, [14b,16] pH, [17] and light, [18] presents substantial challenges in engineering interparticle "bonds". These challenges encompass the selection of intermolecular interactions and the architectural design of surface ligands.…”
Section: Introductionmentioning
confidence: 99%
“…This limits their applications in the field of biology and smart materials. The fabrication of NP assemblies featuring multiple "artificial atoms", well-organized configurations, and responsiveness to external stimuli such as solvents, [15] temperature, [14b,16] pH, [17] and light, [18] presents substantial challenges in engineering interparticle "bonds". These challenges encompass the selection of intermolecular interactions and the architectural design of surface ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, zwitterionic ligands are found on the surface of AuNPs, and exhibit much strong electrostatic attraction to potentially drive pH-triggered aggregation of large AuNPs. [25][26][27] Therefore, it is highly desirable to further investigate the use of zwitterionic ligands for AuNP functionalization that can undergo self-assembly in bacterial infection sites for photothermal therapy (PTT).…”
Section: Introductionmentioning
confidence: 99%
“…Designing and forming nanoparticle films with defined spacing, order, and orientation will enable a large number of nanoparticle-based technologies. , Self-assembly is an essential strategy used to synthesize 2D and 3D nanoscale structures and is mediated by interactions such as van der Waals and electrostatic forces. , The self-assembly of the nanoparticles into larger structures is primarily determined by the size and shape of the nanoparticle core . The effects of solvent and temperature on nanoparticle ligand shells can also significantly impact nanoparticle interactions in solution and morphology in 2D films. Many studies have shown increased control over nanoparticle self-assembly by modifying nanoparticle surface chemistry, , applying external stimuli (e.g., light or magnetic fields), and/or incorporating additives (e.g., polymers or salts) , to drive the self-assembly process. However, much remains to be understood regarding nanoparticle mixing interactions.…”
Section: Introductionmentioning
confidence: 99%
“…5 The effects of solvent and temperature on nanoparticle ligand shells can also significantly impact nanoparticle interactions in solution and morphology in 2D films. 6−8 Many studies have shown increased control over nanoparticle self-assembly by modifying nanoparticle surface chemistry, 9,10 applying external stimuli (e.g., light or magnetic fields), 10−13 and/or incorporating additives (e.g., polymers or salts) 10,14−16 to drive the self-assembly process. However, much remains to be understood regarding nanoparticle mixing interactions.…”
Section: ■ Introductionmentioning
confidence: 99%